Subspace-restricted singular value decompositions for linear discrete ill-posed problems - Hochstenbach, Michiel E.; Reichel, Lothar (Journal of computational and applied mathematics, 2010)
The truncated singular value decomposition is a popular solution method for linear discrete ill-posed problems. These problems are numerically underdetermined. Therefore, it can be beneficial to incorporate information about the desired solution into the solution process. This paper describes a modification of the singular value decomposition that permits a specified linear subspace to be contained in the solution subspace for all truncations. Modifications that allow the range to contain a specified subspace, or that allow both the solution subspace and the range to contain specified subspaces also are described.